Lipoprotein apheresis in the management of severe hypercholesterolemia and hyperlipoproteinemia(a)—The Portuguese experience. Issue 5 (October 2018) - Ferreira, Lia; Palma, Isabel; Bacelar, Conceição; Queirós, José Alexandre; Madureira, Anselmo; Oliveira, José Carlos; Ramos, Maria Helena; Cardoso, Helena
Abstract: Background: Low-density lipoprotein cholesterol (LDL-C) and lipoprotein(a) (Lp(a)) are established causal risk factors for cardiovascular disease (CVD). Lipoprotein apheresis is often required for treatment of patients with a high risk for CVD due to hypercholesterolemia and/or hyperlipoproteinemia(a). Aim: To describe our experience with lipoprotein apheresis in patients with severe hypercholesterolemia or with hyperlipoproteinemia(a). Methods: We retrospectively investigated patients treated with Lipoprotein apheresis using direct adsorption of lipoproteins (DALI) technique, between December 2008 and March 2018, in our center. Adverse events, acute and long term reductions in lipid parameters were analyzed. Results: Between December 2008 and March 2018, a total of 950 treatments were performed in five patients, four with heterozygous familial hypercholesterolemia (HeFH), all on maximally tolerated cholesterol-lowering drug therapy and in one patient with hyperlipoproteinemia(a) and progressive CVD. In the four patients with HeFH we obtained mean acute reductions in LDL-C and non-high-density lipoprotein cholesterol (non-HDL-C) of 62.0 ± 7.8% and 60.4 ± 6.8%, respectively. Regarding long-term efficacy we achieved a mean reduction of 43.1% in LDL-C and of 41.2% in non-HDL-C. In the patient with hyperlipoproteinemia(a) we attained mean acute reductions of 60.4 ± 6.4% in Lp(a) and of 75.4 ± 7.3% in LDL-C per session and long term reductions in Lp(a) and LDL-C of 67.4% and 40.5%, respectively. Adverse events were recorded in only 1.2% of treatments. Conclusion: Lipoprotein apheresis is an efficient and safe treatment in severely hypercholesterolemic patients who are refractory to conservative lipid-lowering therapy or with hyperlipoproteinemia(a) and progressive CVD.